2021
DOI: 10.1177/10775595211049795
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Neglect and Health Risk

Abstract: This study examined relationships between adolescent neglect and abuse and later health risk in a sample of 1050 youth (53% female, 56% Black, and 24% White) from the Longitudinal Studies of Child Abuse and Neglect. At age 16, the youth reported any adolescent exposure to neglect and physical, sexual, and emotional abuse. At age 18, they reported risk behaviors (delinquency, substance use, and sexual behavior) and emotional and behavioral problems (externalizing and internalizing problems, suicidality). Contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…A moderate positive association was found between selfreported sexual abuse and anxiety/depression and thought problems, as well as a weak positive association between sexual abuse and social problems. These results are consistent with other studies showing that exposure to child maltreatment is significantly associated with a higher degree of anxiety-depressive symptoms, as well as aggressive and antisocial behavior (Afifi et al, 2019;Child Welfare Information Gateway, 2019;Fagan, 2019;Herrenkohl et al, 2017;Horan et al, 2014;Iniguez & Stankowski, 2016;Kobulsky at al., 2021;Zolog et al, 2011). It is possible that abused children and adolescents adopt aggressive forms of behavior and themselves become bullies (Spatz Widom, 2015;Yang et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A moderate positive association was found between selfreported sexual abuse and anxiety/depression and thought problems, as well as a weak positive association between sexual abuse and social problems. These results are consistent with other studies showing that exposure to child maltreatment is significantly associated with a higher degree of anxiety-depressive symptoms, as well as aggressive and antisocial behavior (Afifi et al, 2019;Child Welfare Information Gateway, 2019;Fagan, 2019;Herrenkohl et al, 2017;Horan et al, 2014;Iniguez & Stankowski, 2016;Kobulsky at al., 2021;Zolog et al, 2011). It is possible that abused children and adolescents adopt aggressive forms of behavior and themselves become bullies (Spatz Widom, 2015;Yang et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Multiple adverse childhood experiences can disrupt adequate development of selfregulation skills (Kavanaugh et al, 2016;Marusak et al, 2015) or lead to disruption of attachment patterns (Doyle & Cicchetti, 2017;Özcan et al, 2016). Consequently, it could lower self-esteem and social competency skills (Greene & Jones, 2015), which increases the risk for development of psychopathological symptoms later in life, including anxiety, depression, suicidality, posttraumatic stress disorder (Child Welfare Information Gateway, 2019;Kobulsky at al., 2021), and antisocial behavior and delinquency (Greene & Jones, 2015;Herrenkohl et al, 2017;Kobulsky at al., 2021). Children who experience maltreatment are at risk of the development of substance use problems and disorder in adolescence and adulthood (Cicchetti & Handley, 2019).The psychosocial and psychopathological consequences of abuse can hinder the proper development of these children for many years (World Health Organization, 2014) and could lead to transgenerational transmission of abusive behavior (Yang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the factors associated with high-risk behavior, risk behavior profiles, and causal relationships have been studied more comprehensively among general adolescents than the sub-population of adolescents in out-of-home care (Blankenstein et al, 2020;Goulet et al, 2020;Murray et al, 2021). This leads to the assumption that care leavers exhibit more forms of high-risk behavior than have currently been described due to multiple factors which can predispose them to high-risk behavior (Kobulsky et al, 2022). This shortcoming can be attributed to the fact that care leavers are a difficult group to manage and have commit to research.…”
Section: Reason For Placementmentioning
confidence: 99%
“…Several factors have been shown to be associated with high-risk behaviors (e.g., Meeus et al, 2021;Murray et al, 2021;Tinner et al, 2021); these include behavioral, activity, and attention disorders, along with antisocial behavior (Song et al, 2021;Sultan et al, 2021). The underlying causes of behavioral disorders are complex; however, childhood abuse and neglect are important factors in the development of these disorders (García et al, 2021;Kobulsky et al, 2022). Untreated or medically neglected behavioral disorders can adversely affect the development of a child, as well as the transition period of adolescence (Okumura et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Hidalgo et al (2022) showed structural and diffusion-weighted brain morphological measures after harsh parenting were associated with smaller total gray and cerebral white matter and amygdala volumes but not changes in hippocampal or other microstructural metrics in children. With adolescents, Kobulsky et al (2022) found neglect was associated with later mental health disorders (such internalizing and externalizing problems and suicidality) and high-risk behaviors (sexual abuse, risky sexual behavior, and delinquency). With these articles and others, one can imagine potential pathways linking outcomes across years and generations.…”
Section: Biology Risk Factors and Behaviormentioning
confidence: 99%